Persepsi Orang Tua dalam Menghadapi Pembelajaran Tatap Muka di Taman Kanak-Kanak pada Masa Pandemi Covid-19 - Ervin Nurul Affrida; Abd Cholid; A'inur Rofida Salsavira (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2022)
The Covid-19 pandemic has had an impact on various fields, one of which is education. In the Early Childhood Education (PAUD) unit in the Academic Year 2022/2023 switch from the Learning from Home (BDR) system to Face-to-Face Learning (PTM). Implementation of PTM in PAUD units while complying with government regulations and complying with health protocols. Compliance with health protocols is very important to teach from an early age, especially after the implementation of PTM, children return to activities outside the home. This study aims to determine parents' perceptions of NCDs in children aged 4-6 years. The research method used is descriptive qualitative. Data collection techniques used through questionnaires and interviews.